Reducing the barriers to breastfeeding : an analysis of health services in Northern Ontario - Shields, Kristin E. (My University, 2005)
Given that there is a societal expectation that mothers of newborns initiate and maintain breastfeeding for at least six months, there is a concomitant expectation that society provide the essential services, education, and support systems to ensure breastfeeding success. The purpose of this study was to: 1. Determine the barriers that affect a mother’s decision to initiate breastfeeding and continue breastfeeding for the recommended six months (minimum). 2. Determine if current public health breastfeeding programs sufficient to overcome these harriers. 3. Determine what, if any, changes could be made to public health promotion or education programs to reduce the suggested barriers to breastfeeding. The study used a secondary data analysis of raw data from the Northern Ontario Perinatal and Child Health Survey (NOPCHS) (2003) to resolve the specific questions related to barriers, programs, and recommended changes. Regression analysis was used to first determine whether or not a mother chose to breastfeed, and second to determine how long a mother breastfed, exclusively. The results from the regression analysis suggested that a mother’s choice to breastfeed was based on whether she wished to increase her bonding with her child; whether she was comfortable breastfeeding in public places; whether she was in good health; and the level of her partner’s education. Likewise, the regression output identified that the length of time a mother breastfed was determined by a mother reporting an inadequate supply of milk; the child weaning him/herself; whether a mother felt comfortable breastfeeding in the mall; the mother’s confidence with breastfeeding at hospital discharge; whether the mother used of the Healthy Babies, Healthy Children program; the number of cigarettes the mother smoked; reported fatigue or inconvenience of breastfeeding by the mother; a plan to stop at the time when child was weaned; whether the mother worried about insufficient milk supply; the mother’s attendance at prenatal classes; the mother’s comfort breastfeeding at the workplace; awareness of breastfeeding drop-ins; the choice to breastfeed for cost efficacy; and the mother having the support of a lactation consultant. With respect to Research Question 2 (Determine if current public health breastfeeding programs sufficient to overcome these barriers), the results indicate that only 16% of the respondents continued to breastfeed at six months (the minimum duration recommended by the World Health Organization). This finding suggests that current public health breastfeeding programs are not sufficient to overcome the barriers to breastfeeding. Finally, based on the specific responses to questions in the NOPCHS and from previous studies reported in the literature, it is suggested that breastfeeding programs must be relevant; available to assist and provide support to mothers; be explicit; widely advertised and easily accessible; and promote a culture that supports mothers in their decision to breastfeed, while providing information to the general public on the benefits of breastfeeding, promoting acceptance of this natural behaviour.
Keywords: Breastfeeding (Psychological aspects); Breastfeeding promotion (Ontario, Northern)